DAMPAK JANGKA PENDEK PANDEMI COVID-19 TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DAN INDEKS SEKTORAL - Khairunnisa Nadhifah Syahfiraputri; Harjum Muharam (Diponegoro Journal of Management, 2022)
The study aims to analyze the short-term impact of the Covid-19 pandemic on the Composite Stock Price Index and Sectoral Indexs. This study calculated the expected return and abnormal return from each industry sector with the capital asset pricing model (CAPM) formula. From the results of the count can also be calculated Cummulative Abnormal Return (CAR) and Cummulative Average Abnormal Return Market (CAARM). The results of the study were divided into several sub-windows with the timeline of the Indonesian government's policy in dealing with the Covid-19 pandemic. The results showed that the Covid-19 Pandemic had a significant negative effect on the Composite Stock Price Index and Sectoral Index in certain sub-windows.